RANCANG BANGUN ALAT SORTASI OTOMATIS UNTUK BUAH TOMAT MENGGUNAKAN APLIKASI IMAGE PROCESSING - Yultrisna Yultrisna; Andi Syofian (Situs resmi ITP Press, 2016)
One of the stages of post-harvest activities were quite decisive is sorting. This process includes the separation of the product based on one or several criteria. Particularly in tomatoes, color and size parameters determine the quality of the fruit commodities. Along with the development of science and technology today, many developed with the sorting process automation systems for effectiveness in the use and accuracy of the results obtained. Tomato sorting machine which is realized using the camera as a sensor, the camera will take a picture of tomatoes through in line, and then a camera will be able to distinguish color and size of the tomatoes. Determination of color in tomatoes is doing by using the method of determining the threshold and size of tomato using edge detection method. Sorting is done by a servo motor to perform the separation of the tomatoes that have been detected in tomato set output based on the position that has been determined. Controlling which gave the order for the servo motor work is PIC16F84A microcontroller using serial data communication from the PC to the microcontroller. Testing the system as a whole to test the consistency of the performance of the machine have been conducted using seven different criteria of tomatoes with three times repetitions with successful results for 71% edge detection method, the grouping size is 100% and 95% for color readings